Les représentations de Mars Ultor sur les pierres gravées - Girard, Thibault, 1984- (Archaeopress Roman archaeology ;, 2023)
Gems representing the Mars Ultor type were produced between the 1st and 4th centuries. Scattered around the world, the 240-odd engraved stones gathered here attest to the longevity and impact of the Augustan image in Roman iconography and allow us to follow the variations in meaning of the motif.